Genome-Wide Association Study in Vestibular Neuritis: Involvement of the Host Factor for HSV-1 Replication - Rujescu, Dan; Hartmann, Annette M.; Giegling, Ina; Konte, Bettina; Herrling, Marko; Himmelein, Susanne; Strupp, Michael (Frontiers in Neurology, 2018)
Objective: In order to identify genetic variants associated with vestibular neuritis, a common cause of peripheral vertigo with a potential causative link to the reactivation of herpes simplex type 1 (HSV-1), we conducted a genome-wide association study. Methods: Association was assessed using approximately 8 million variants. 131 patients with vestibular neuritis and 2,609 controls of European ancestry were included. Results: Genome-wide associations with vestibular neuritis were detected in 4 regions containing protein coding genes assignable to two functional groups: virus hypothesis and insulin metabolism. Genes of set 1 are related to viral processes: nuclear receptor subfamily 3 group C member 2 (NR3C2) is a receptor for mineralocorticoids and glucocorticoids and was shown to be a host factor for HSV-1 replication. Ankyrin repeat domain 30A (ANKRD30A) encodes a host factor for human immunodeficiency virus-1 (HIV-1) infection. It shows rapid evolution and is induced by interferon stimulation. Mediator complex 30 (MED30), an important member of the mediator complex, has been shown to be involved in replication of HIV-1, a knockdown leading to impaired viral replication. The second set of genes LIM homeobox transcription factor 1 alpha (LMX1A), solute carrier family 30 member 8 (SLC30A8) is associated with insulin metabolism and resistance, a feature of some patients in whom type 2 diabetes is an accompanying comorbidity of vestibular neuritis. Conclusions: Using a GWAS approach to evaluate the etiology of vestibular neuritis these findings provide another piece of evidence that it may be caused by a viral inflammation.